Role of age and gender in forgiveness during student life (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The study measured the role of age and gender in forgiveness during student life involving a 2x2 between-group factorial design comprising of a convenience sample of 200 student participants, where 100 (47 girls, 53 boys) were from the age groups of 13 to 15 years and 100 (63 girls, 37 boys) from 18 to 20 years from two leading educational institutions in Hyderabad. The students completed a survey assessing the forgiveness and its three domains–forgiveness of self, others, and situations. The results revealed a significant main effect of age in respect of forgiveness indicating that the older students scored higher in forgiveness compared to their younger counterparts. The older students also scored significantly higher in forgiveness of self and forgiveness of situation in comparison to their younger counterparts. Gender was found to play a significant role in determining neither the level of forgiveness nor its domains during student life.